PENINGKATAN PENGETAHUAN TENAGA KESEHATAN TENTANG PROGRAM VAKSINASI COVID-19 DI INDONESIA - Efendi, Ferry; Dewi, Yulis Setiya; Ariï¬n, Hidayat; Hargono, Arief; Apriyanto, Yogo; Adnani, Qorinah Estiningtyas Sakilah; Gudia, Amel Dawod Kamel (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The increasing number of cases and deaths due to Covid-19 has become a global problem. The Covid-19 vaccination program becomes one of the efforts by the government to save lives and protect the citizens. The safety, effectiveness, and postvaccination impact are often discussed and debated by the community. This community service aimed to increase the knowledge of health workers regarding the Covid-19 vaccine in Indonesia. This activity was attended by 26 nursing students and was carried out virtually. The evaluation of participants' knowledge was carried out using a knowledge questionnaire consisting of 10 questions related to knowledge of the Covid-19 vaccination. The analysis was performed by paired t-test. The results of community service showed that the socialization participants were enthusiastic and motivated nurses as one of the health workers to play an essential role to deliver the appropriate information promotions to assist the government in achieving vaccination programs. The level of knowledge of participants increased after being given socialization (p-value 0.000). The government and health workers are the basis for program preparation and appropriate information to achieve the vaccination target in Indonesia.